A simple, accurate and universal method for quantification of PCR. Issue 1 (December 2016) - Boulter, Nicky; Suarez, Francia; Schibeci, Stephen; Sunderland, Trevor; Tolhurst, Ornella; Hunter, Tegan; Hodge, George; Handelsman, David; Simanainen, Ulla; Hendriks, Edward; Duggan, Karen
Abstract Background Research into gene expression enables scientists to decipher the complex regulatory networks that control fundamental biological processes. Quantitative real-time PCR (qPCR) is a powerful and ubiquitous method for interrogation of gene expression. Accurate quantification is essential for correct interpretation of qPCR data. However, conventional relative and absolute quantification methodologies often give erroneous results or are laborious to perform. To overcome these failings, we developed an accurate, simple to use, universal calibrator, AccuCal. Results Herein, we show that AccuCal quantification can be used with either dye- or probe-based detection methods and is accurate over a dynamic range of ≥105 copies, for amplicons up to 500 base pairs (bp). By providing absolute quantification ofall genes of interest, AccuCal exposes, and circumvents, the well-known biases of qPCR, thus allowing objective experimental conclusions to be drawn. Conclusion We propose that AccuCal supersedes the traditional quantification methods of PCR.